O tráfico também é feminino!: Aproximações ao trabalho das mulheres no comércio varejista de drogas - Naiara Cristiane da Silva (2015)
This study aimed to analyze the work activity of women in drug trafficking as well as the senses of work and psychosocial impacts involved in adhering to this activity. The field research was conducted at the Association for the Protection and Assistance Condemned (APAC) female located in Itaúna with life history collection and observation of women prisoners as a result of drug trafficking. This study-guided in the prerogative that drug trafficking is organized and structure as work activity now represents possibility of labor insertion also for women albeit informal and illegal way. Retail trade in drugs as hegemonic masculine space opens the doors of their "firms" for the entry of women who come to participate in the precise form of marginal economy and income generation provided by the drug industry. In this sense, the drug trade is analyzed in this study based on cyclical and structural issues that demonstrate the growing participation of women in the drug business is most often rooted in deep social inequalities, which can not be separated from economic globalization and precarizações the growing world of work. Currently drug trafficking is the activity that more women forward for the imprisonment and understanding bases remain obscure and made invisible. Features gender linked to representations of criminal woman contribute to the inevitable allocation of entry and permanence of women in this activity with the male presence which contributes to the victimization of women. It was intended through this study denaturalize the usual binding recognizing women in active subjects and protagonists, with possibilities of autonomy in their choices.